Incidence, Treatment, and Outcome Trends of Necrotizing Enterocolitis in Preterm Infants: A Multicenter Cohort Study - Zozaya, Carlos; García González, Inés; Avila-Alvarez, Alejandro; Oikonomopoulou, Niki; Sánchez Tamayo, Tomás; Salguero, Enrique; Saenz de Pipaón, Miguel; García-Muñoz Rodrigo, Fermín; Couce, María L. (Frontiers in Pediatrics, 2020)
Background: Data regarding the incidence and mortality of necrotizing enterocolitis trends are scarce in the literature. Recently, some preventive strategies have been confirmed (probiotics) or increased (breastfeeding rate). This study aims to describe the trends of necrotizing enterocolitis incidence, treatment and mortality over the last decade in Spain. Methods: Multicenter cohort study with data from the Spanish Neonatal Network - SEN1500 database. The study period comprised from January 2005 to December 2017. Preterm infants < 32 weeks of gestational age at birth without major congenital malformations were included for analysis. The main study outcomes were Necrotizing enterocolitis incidence, co-morbidity (bronchopulmonary dysplasia, late-onset sepsis, cystic periventricular leukomalacia, retinopathy of prematurity, acute kidney injury), mortality and surgical / non-surgical treatment. Results: Among the 25,821 included infants, NEC incidence was 8,8% during the whole study period and remained stable when comparing the 3-year subperiods. However, more cases were surgically treated (from 48.8% in 2005-08 to 70.2% in 2015-17, p<0.001). Mortality improved from 36.7% in the 2005-2008 to 26.6% in 2015-2017 (p<0.001). Breastfeeding rates improved over the studied years (24.3% to 40.5%, p<0.001), while gestational age remained invariable (28.5 weeks, p=0.20). Prophylactic probiotics were implemented during the study period in some units, reaching 18.6% of the patients in 2015-17. Conclusions: The incidence of necrotizing enterocolitis remained stable despite the improvement regarding protective factors frequency. Surgical treatment became more frequent over the study period, whereas mortality decreased.